The Effect of the Thinking Aloud Pair Problem-Solving Learning Model on Students’ Mathematical Problem-Solving Outcomes - Nabila Fitria; Fibri Rakhmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to determine the effect of the Thinking Aloud Pair Problem-Solving learning model on the mathematical problem-solving ability of seventh-grade students at SMP Negeri 5 Mandau. The method used was quantitative with a quasi-experimental approach. The research design was a pre-test post-test only control group. The research instrument consisted of test questions. The results of the study show that the implementation of the Thinking Aloud Pair Problem-Solving model significantly increases students’ mathematical problem-solving ability compared to the conventional method. Based on the research findings regarding the implementation of the Thinking Aloud Pair Problem Solving learning model in mathematics learning at SMP Negeri 5 Mandau, it can be concluded that the model has an effect on improving the mathematical problem-solving ability of seventh-grade students in algebra material